Validation of two short questionnaires assessing physical activity in colorectal cancer patients - Hege Berg Henriksen; Sveinung Berntsen; Ingvild Paur; Manuela Zucknick; Anne Juul Skjetne; Siv Kjølsrud Bøhn; Christine Henriksen; Sigbjørn Smeland; Monica Hauger Carlsen; Rune Blomhoff (BMC, 2018)
Abstract Background In order to investigate the impact of adherence to recommendations of physical activity and sedentary time on health outcomes in clinical trials, there is a need for feasible tools such as questionnaires that can give representative estimates of these measures. The primary aim of the present study was to validate two such questionnaires and their ability to estimate adherence to the recommendations of physical activity defined as moderate-to- vigorous physical activity or moderate physical activity of at least 150 min/week in colorectal cancer patients. Secondarily, self-reported sedentary time from the HUNT-PAQ was also evaluated. Methods Participants from 'The Norwegian dietary guidelines and colorectal cancer survival-study' (CRC-NORDIET study) completed two short questionnaires; the NORDIET-FFQ (n = 78) and the HUNT-PAQ (n = 77). The physical activity monitor SenseWear Armband Mini was used as the reference method during seven consecutive days. Results The NORDIET-FFQ provided better estimates of time in moderate-to- vigorous physical activity and moderate physical activity than the HUNT-PAQ. The NORDIET-FFQ was unable to rank individual time in moderate-to- vigorous physical activity and moderate physical activity (Spearman's rho = 0.08, p = 0.509 and Spearman's rho rho = 0.01, p = 0.402, respectively). All intensities were under-reported by the HUNT-PAQ, but ranking of individual time in moderate physical activity and sedentary time were acceptable among women only (Spearman's rho = 0.37, p = 0.027 and Spearman's rho = 0.36, p = 0.035, respectively). The HUNT-PAQ correctly classified 71% of those not meeting the recommendations (sensitivity), and the NORDIET-FFQ correctly classified 63% of those who met the recommendations (specificity). About 67% and 33% reported to meet the recommendation of moderate-to- vigorous physical activity with the NORDIET-FFQ and HUNT-PAQ, respectively, whereas 55% actually met the moderate-to- vigorous physical activity according to the SenseWear Armband Mini. Conclusions The NORDIET-FFQ provided better specificity and better estimates of PA than the HUNT-PAQ. The HUNT-PAQ provided better sensitivity, and provided better ranking of PA and sedentary time among women than NORDIET-FFQ. It is important to be aware of the limitations documented in the present study. Trial registration The study is registered on the National Institutes of Health Clinical Trials (Identifier: NCT01570010). Registered 4 April 2012.